IMPLEMENTASI SISTEM INFORMASI DONASI MINYAK JELANTAH (SIMINAH) BERBASIS DIGITAL DI KOTA DUMAI DENGAN PENDEKATAN LEAN SOFTWARE DEVELOPMENT - Ramadhani, Shumaya Resty; Hanifah, Puja; Yuliska, Yuliska; Najwa, Nina Fadila; Hartanto, Boby; Syaliman, Khairul Umam (Jurnal Komputer Terapan, 2024)
Used cooking oil, or waste cooking oil, is the byproduct of repeatedly using cooking oil, which results in the formation of substances harmful to the body. Furthermore, improper waste cooking oil management poses a risk of environmental pollution. To address this issue, PT. Kilang Pertamina Internasional Refinery Unit II Dumai (PT. KPI RU II), through its Corporate Social Responsibility (CSR) program, initiated the "Sedekah Jelantah" program. This initiative involves the CSR division, several sub-districts in Dumai Timur, and the general public, aiming to raise awareness about environmental pollution and promote urban greening in Dumai. To support the program's implementation, a digital system is essential to efficiently manage the donation flow of waste cooking oil from upstream to downstream. Therefore, an integrated web and mobile-based information system, called Sistem Informasi Minyak Jelantah (SiMINAH), was developed using the Lean Software Development (LSD) methodology. Blackbox testing, user acceptance testing (UAT), and usability testing were conducted to ensure the system's quality. The black box testing and UAT results revealed that 100% of the application functions performed well and met stakeholder expectations. The usability test showed 87.3%, indicating that the system is highly feasible and meets user needs. All users provided positive feedback on SiMINAH, noting that it simplifies waste cooking oil donations and enhances management processes for local sub-districts and the Dumai city CSR team.